The utilization of Noni Fruit (Morinda citrifolia L) As the Ice Cream ingredient - Anita Juhari; Rodliyati Azrianingsih; Amin Setyo Leksono (Biotropika: Journal of Tropical Biology, 2017)
Abstract The objectives of this research were to determine of the society perception on the use of noni fruit and ice cream, technique to produce ice cream on processed products of noni, to know the content of the nutritional value of noni ice cream, as well as society prospects and perception toward noni ice cream products. The method of this research used a questionnaire survey involving semi structure direct interviews, marketing and beneficial calculation of noni ice cream products. The data were presented in graphical form followed by feasibility analysis. After the survey, 81% of respondents liked and interested in consuming ice cream noni products. Noni fruit mixture was added into the ice cream processed analyses showed that noni ice cream product healthier and have a high nutrient. Fat content of noni ice cream at 6.54 % and lower than the SII standard of 8 %, which indicated that the noni ice cream was low fat. Noni ice cream contain 36,89 mg/100g of vitamin C. most respondents favored  texture of noni ice cream at 69.9 %  and taste of noni ice cream at 54.50 % while products the ice cream by mixing 15% respectively noni fruit texture. Noni ice cream selling during one month resulted profits at 42.200 IDR. Analysis of feasibility noni ice cream was at 1.27 (> 1) which indicated that the business of ice cream noni products was feasible to be continued and carried out the development of the product. Keywords: business, ice cream, marketing, noni, processing